Die pactum successorium: stiefkind van die Suid-Afrikaanse reg - Rautenbach, Christa (Koers, 1999)
The pactum successorium: stepchild of South African lawSouth African law does not generally permit a testator to bequeath his estate by means of contract. This rule flows from the general rule in Roman Law that an estate must devolve either by will or in terms of the law governing intestate succession. Despite the prohibition against succession pacts there have been numerous attempts by contracting parties to regulate devolution of their estates inter vivos by means of contract. Such contracts are commonly called pacta successoria and have been regarded as contra bonos mores and invalid since early law. Although a number of reasons have been put forward for the maintaining of the prohibition against pacta successoria, the main reason for the aversion against the pactum successorium is the fact that they interfere with the testator’s freedom of testation. It is suggested that the existing law in South Africa with regard to the pactum successorium should be changed. This calls for a reappraisal of the principle of freedom of testation. It is clear that South African law takes this principle much further than is the case in other legal systems such as in England and Germany. Furthermore, the South African devotion to the principle of freedom of testation appears strange in view of the obvious conflict with the principle of freedom of contract. Finally, it is suggested that the common law prohibition against the pactum successorium should be abolished. Since it is clear from the attitude of the courts so far, this can only be effected by legislature.